STUDI KENDALA AGRIBISNIS BAWANG MERAH DI DESA TALANG IPUH KECAMATAN SUAK TAPEH KABUPATEN BANYUASIN - Nasution, Doli Indra; Iswarini, Harniatun; Afriyatna, Sisvaberti (Universitas Muhammadiyah Palembang, 2016)
Study of Challots Agribusiness Constraints in Talang Ipuh Village Suak Tapeh Districts Banyuasin Regency. This study aims to determine how the system challots agribusiness and to find out what are the constraints of agribusiness challots in village Talang Ipuh districts of Suak Tapeh Banyuasin Regency. Sampling methods were calculated using census, information retrieval method of the total population and the population in small quantities, the sample is farmers who cultivate onion in village Talang Ipuh districts of Suak Tapeh Banyuasin Regency as many as 14 farmers were taken entirely. Methods of data collection were interviews, data collected in this study included primary data and secondary data. Primary data obtained from respondents through direct interviews and field abservations accompanied by a list of questions has been provided while secondary data obtained from institutions or authorities relating to the research. Methods of processing and analysis of data, to answer the firs and second issues, use descriptive analysis with qualitative approach. Research shows that agribusiness challots consists of subsystems provision of means of production, which consists of challots seeds, fertilizers, farm equipment, and labor. Subsystem farming activities carried out from cultivation to harvesting. Marketing subsystem is how the system of sales made by the farmers. Constraints faced in the provision of means of production subsystems, namely seeds and fertilizers, the farm subsystems, namely irrigation and lack of education, and the lack of marketing subsystem merchant wholesalers or middlemen.